New adjuvant technology for pesticide use on wine grapes - Gaskin, R.E.; Manktelow, D.W.; Elliott, G.S. (New Zealand Plant Protection, 2002)
Wine grape growing is under increasing pressure to reduce pesticide use A project was undertaken to develop new adjuvant prescriptions to reduce spray volumes required throughout fullseason pesticide programmes in vineyards and to improve spray coverage and retention on foliage and grape bunches A preharvest field trial confirmed improved targeting of Chardonnay foliage and bunches with markedly lowered spray application volumes when a novel organosilicone adjuvant DuWett was included in the spray mix Application volumes of le;200 litres/ha maximised retention and distribution of pesticide sprays containing the organosilicone The optimal DuWett rate required in sprays targeting foliage was lower (0204 litres/ha) than that in sprays directed at grape bunches (0208 litres/ha) The results suggest spray application volumes on grapes could be greatly reduced with use of appropriate adjuvants without compromising pesticide efficacy